UPAYA MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA DI LINGKUNGAN PENGAWAS PEMILIHAN UMUM KECAMATANLINGGO SARI BAGANTI DALAM MEWUJUDKAN PEMILIHAN UMUM YANG LANGSUNG, UMUM, BEBAS, RAHASIA, JUJUR DAN ADIL - Rahmatullah Pratama; Dike Rama Putra, Widia Firta (Adiba Aisha Amira, 2023)
The aim of community service activities is to implement one of the Tri Dharmas of Higher Education. This service makes a contribution to both the community and the team in improving the quality of human resources to realize smart general elections. It is hoped that the knowledge gained from this service will be able to provide enthusiasm and motivation so that the general elections will run honestly and fairly.